Motivation and Use of Telehealth Among People with Depression in the United States - Soumitra S. Bhuyan; Saurabh Kalra; Asos Mahmood; Akash Rai; Kahuwa Bordoloi; Urmi Basu; Elizabeth O'Callaghan; Marilyn Gardner (SAGE Publishing, 2024)
Introduction: The global mental health crisis, compounded by the challenges of the COVID-19 pandemic, underscores the urgent need for accessible mental health care solutions. Telehealth services have emerged as a promising technology to address barriers to access mental health services. However, population-based studies examining telehealth utilization among individuals with depression are limited. Methods: Using data from the National Cancer Institute's Health Information National Trends Survey (HINTS) of 2022 (n = 4502), we investigated telehealth utilization among individuals diagnosed with depression in the United States. We employed multivariable logistic regression analysis to assess the association, adjusting for demographics, health behaviors, health status, trust in the medical system, and access to transportation. We also studied the factors that motivated the use of telehealth among individuals diagnosed with depression. Results: In the multivariable adjusted logistic regression models, individuals diagnosed with depression (AOR 2.59, 95% CI 1.96-3.42) were significantly more likely to use telehealth services relative to individuals with no depression diagnosis. Other factors associated with increased telehealth use included women (AOR 1.36, 95% CI 1.07-1.72), Hispanic ethnicity (AOR 1.78, 95% CI 1.28-2.48), being married or living with a partner (AOR 1.30, 95% CI 1.05-1.62), frequent healthcare visits (AOR 2.31, 95% CI 1.71-3.11), health insurance coverage (AOR 1.86, 95% CI 1.04-3.34), confidence in self-care (AOR 1.38, 95% CI 1.07-1.78), and lack of reliable transportation (AOR 1.57, 95% CI 1.01-2.42). Major motivation factors that influenced telehealth use among individuals with depression primarily included convenience, such as reduced travel times, as well as clinicians' recommendations. Conclusion: Telehealth is a promising option for accessing mental health care, particularly for those with depression. Further research is needed to understand how well telehealth works and how it can be combined with traditional care, ensuring fair costs and keeping information safe.